2022
DOI: 10.1002/adma.202206349
|View full text |Cite
|
Sign up to set email alerts
|

Metal Confined in 2D Membranes for Molecular Recognition and Sieving towards Ethylene/Ethane Separation

Abstract: lenge for 2D-material membranes to separate mixtures of molecules with extremely close physical properties and kinetic diameters owing to the lack of size-sieving properties and specific affinity of the 2D nanochannels. For instance, towards ethylene/ethane separation, the current distillation technology is very energy-consuming and concurrently increases carbon dioxide emissions. [8] It is considered as one of the seven chemical separations that if improved can reap great global benefits. [9] The most widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Surprisingly, the interlayer spacings of the GO–PEI membrane were limited to 10.80 Å in the wet state, far smaller than 11.59 Å of the GO membrane. The thickness of the GO monolayer (a) is 3.35 Å, as reported . Thus, the effective size of the GO–PEI nanochannel is 7.45 Å, which is very close to the hydrated ion diameter of Li + , whereas much smaller than that of Mg 2+ .…”
Section: Results and Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Surprisingly, the interlayer spacings of the GO–PEI membrane were limited to 10.80 Å in the wet state, far smaller than 11.59 Å of the GO membrane. The thickness of the GO monolayer (a) is 3.35 Å, as reported . Thus, the effective size of the GO–PEI nanochannel is 7.45 Å, which is very close to the hydrated ion diameter of Li + , whereas much smaller than that of Mg 2+ .…”
Section: Results and Discussionsupporting
confidence: 74%
“…The thickness of the GO monolayer (a) is 3.35 Å, as reported. 29 Thus, the effective size of the GO−PEI nanochannel is 7.45 Å, which is very close to the hydrated ion diameter of Li + , whereas much smaller than that of Mg 2+ . These results could be attributed to the electrostatic and crosslinking effects between the PEI molecular chain and GO nanosheets in the lamellar structure of the GO−PEI membrane, which prevented the swelling between pristine GO lamellas.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Overcoming the limitations of polymeric membranes, separation membranes constructed by two-dimensional (2D) materials have exhibited unique attributes in precise molecular sieving owing to their unique nacre-like structures and ultrafast mass transport. As typical 2D materials, graphene-based membranes consisting of an atom-thick 2D carbon lattice and oxygen functional groups have emerged as candidates for nanofiltration due to unimpeded water permeation, excellent chemical resistance, easy solution processability, and mechanical strength. Functionalized 2D membranes with advanced performances have achieved great progress and shown potential in many applications. Recently, several pioneering works have focused on developing polymer-decorated 2D membranes to modulate the permeation of water and ion molecules by external stimuli such as pH, gas, light, and temperature. However, most previous attempts were based on modulating the molecular configuration or surface hydrophilicity of graphene-based membranes. , Moreover, similar to the polymer-based membranes, the response of polymer-decorated graphene-based membranes often takes tens of minutes (>30 min) to respond to external factors and restore to the original state, owing to the diffusion of signal chemicals and the relaxation of polymer chains. Therefore, fast, reversible, and remote control of graphene-based membranes are highly desired in practical applications. Zhou et al developed a fast-response graphene oxide (GO) based membrane to electrically control water permeation by introducing conductive filaments via electrical breakdown and ionizing the water cluster within the 2D capillary . Meanwhile, Li et al demonstrated a nanoporous graphene-based membrane to accelerate ion diffusion by modulating the interfacial electrical double layer under an external electrostatic field .…”
mentioning
confidence: 99%